2019
DOI: 10.3390/land8090141
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Controlling Factors of Valley Bottom Gullies

Abstract: Valley bottomland provides diverse agricultural and ecosystem benefits. Due to concentrated flow paths, they are more vulnerable to gully erosion than hillslope areas. The objective of this review was to show what caused valley bottoms gullies and to present deficiencies in existing rehabilitation measures. From the literature review, we found the following general trends: watershed characteristics determine location of valley bottom gullies; an increase in water transported from the watershed initiates the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 114 publications
(151 reference statements)
2
28
2
Order By: Relevance
“…The TWI determines soil saturation level which is important for gully erosion but it also does not have that much role to play in this region. Rainfall, lithology and drainage density have been depicted as major drivers of gully erosion by many researchers but in this region these parameters have low to moderate importance on gully erosion (Langendoen et al 2013;Amare et al 2019;Arabameri, Pradhan, and Rezaei 2019a). Therefore, it may be stated that although the key drivers of gully erosion are uniform for all regions some factors are more important for a particular region which may be insignificant for the others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TWI determines soil saturation level which is important for gully erosion but it also does not have that much role to play in this region. Rainfall, lithology and drainage density have been depicted as major drivers of gully erosion by many researchers but in this region these parameters have low to moderate importance on gully erosion (Langendoen et al 2013;Amare et al 2019;Arabameri, Pradhan, and Rezaei 2019a). Therefore, it may be stated that although the key drivers of gully erosion are uniform for all regions some factors are more important for a particular region which may be insignificant for the others.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the Inceptisols near the river induce a quick surface wash of the material. Amare et al (2019) has reported that run-off and sub-surface run-off are one of the main drivers of gully erosion citing examples from ample literatures (Moges and Holden 2008). Distance from road is the second most important variable of head-cut gully erosion here which indicates that anthropogenic interferences in terms of development and construction activity over the land leads to the weakening of soil and then surface run-off erodes it to form gully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they frequently occur in alluvial deposits as a result of subsurface or saturation excess overland flow (e.g. Amare et al, 2019). We therefore also included the average distance of each site to a river as a potential predictor variable.…”
Section: Considered Predictor Variablesmentioning
confidence: 99%
“…For example, in the case of gully erosion, the topographic conditions leading to gully initiation will also depend on local soil and vegetation characteristics and the overall geomorphic setting (e.g. Torri and Poesen, 2014;Rossi et al, 2015;Amare et al, 2019).…”
Section: Introductionmentioning
confidence: 99%